An Essay on Divine Authority - Murphy, Mark C. (Cornell Studies in the Philosophy of Religion Ser, 2018)
Cover -- An Essay on Divine Authority -- Title -- Copyright -- Dedication -- Contents -- PREFACE -- INTRODUCTION: THE PROBLEM OF DIVINE AUTHORITY -- 1 WHAT DIVINE AUTHORITY IS -- 1.1 Reasons and Practical Authority -- 1.2 Theses about Divine Authority -- 2 THE COMPLIANCE THESIS -- 2.1 The Authority Thesis and the Compliance Thesis -- 2.2 The Argument for the Compliance Thesis -- 2.3 Implications of Speech-Acts and Sincerity -- 2.4 Commands and Decisive Reasons for Action -- 2.5 God's Necessary Sincerity -- 3 DIVINE AUTHORITY AND DIVINE PERFECTION -- 3.1 Divine Authority and Perfect-Being Theology -- 3.2 Omniscience -- 3.3 Moral Goodness -- 3.4 Omnipotence -- 3.5 Practical Authority as a Divine Perfection -- 4 DIVINE COMMAND METAETHICS AND THE AUTHORITY THESIS -- 4.1 Moral Philosophy as a Route to the Authority Thesis -- 4.2 Divine Command Metaethics (DCM) -- 4.3 Causal and Supervenience DCM Arguments for the Authority Thesis: Invalid -- 4.4 The Analysis DCM Argument for the Authority Thesis: Valid but Unsound -- 4.5 The Reduction DCM Argument for the Authority Thesis: Valid but Unsound -- 5 MORAL ARGUMENTS FOR THE AUTHORITY THESIS -- 5.1 Moral Principles and Divine Authority -- 5.2 Justice -- 5.3 Property -- 5.4 Gratitude -- 5.5 Coordination -- 5.6 Obedience to God as an Independent Moral Principle -- 6 THE AUTHORITY THESIS AND ORTHODOX CHRISTIANITY -- 6.1 The Stronger and Strong Authority Theses -- 6.2 The Practical Stance toward God Endorsed by Christianity -- 6.3 God's Kingship over Israel -- 6.4 Is an Authority Thesis an Affirmation of Scripture (or Tradition)? -- 6.5 The Presumption against Belief in Authority Relationships -- 7 A SOLUTION TO THE PROBLEM OF DIVINE AUTHORITY -- 7.1 A More Modest Account of Divine Authority -- 7.2 Divine Authority, Loosely Speaking, Is Universal -- 7.3 Divine Authority, Strictly Speaking, Is Not Universal